Analisis Gerakan Serangan yang digunakan Atlet Karate pada Pertandingan Kumite di Perguruan Kushin Ryu M Karate Do Indonesia (KKI) di Kota Lubuklinggau - Mardiana, Indah; Pandra, Viktor; Suhdy, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This study aims to analyze how many attack moves were used by karate athletes when facing a kumite match on Khusyin Ryu M Karate Do Indonesia athletes in Lubuklinggau City. This research method used a qualitative content analysis approach. The population and sample were Kushin Ryum Karate Do Indonesia (KKI) college athletes, totaling 10 athletes with 5 female athletes and 5 female athletes. Data collection techniques in this study used method triangulation. Data analysis techniques used interviews and questionnaires. The results of this study were that the total strokes for men were 43 times with 13 points gaining points and 30 strokes that did not earn points, so that the percentage of strokes was 26%. Whereas in the men's kick attack, they got 16 kicks and none of them got a point with a kick success percentage of 0%. For women's matches, they got 48 attacks with 9 punches that got points and 39 punches that don't got points so that the percentage of success for hits was 18%. Unlike the kick attack 9 times without getting a point so the success rate for kick attacks was 0%. From these data it could be concluded that the most dominant attacks carried out were punches compared to kicks with a percentage of 26% punches and 0% kicks for boys while for girls 18% punches and 0% kicks. It could be seen that the number of attacks that fail compared to attacks that gkt points so contrary to achievement. Keywords: Competition Analysis, Karate, Kumite,